2019
DOI: 10.1016/j.neuroimage.2019.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Automagic: Standardized preprocessing of big EEG data

Abstract: Electroencephalography (EEG) recordings have been rarely included in large-scale studies. This is arguably not due to a lack of information that lies in EEG recordings but mainly on account of methodological issues. In many cases, particularly in clinical, pediatric and aging populations, the EEG has a high degree of artifact contamination and the quality of EEG recordings often substantially differs between subjects. Although there exist a variety of standardized preprocessing methods to clean EEG from artifa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(110 citation statements)
references
References 61 publications
2
108
0
Order By: Relevance
“…Processing of the EEG data was conducted using the EEGLAB toolbox (Delorme and Makeig, 2004) using a similar pipeline as given in Bigdely-Shamlo et al 2015and Callan et al (2018), Pedroni et al (2019), and those suggested on the EEGLAB wiki 1 .…”
Section: Pre-processing and Icamentioning
confidence: 99%
“…Processing of the EEG data was conducted using the EEGLAB toolbox (Delorme and Makeig, 2004) using a similar pipeline as given in Bigdely-Shamlo et al 2015and Callan et al (2018), Pedroni et al (2019), and those suggested on the EEGLAB wiki 1 .…”
Section: Pre-processing and Icamentioning
confidence: 99%
“…The EEG recordings with a 250-Hz sample frequency were first resampled to a sample frequency of 256 Hz using the EEGLAB toolbox in Matlab [13]. Second, to remove slow-wave drifts and high amplitude non-brain activity from the EEG data, a forward-backward filter as well as ASR (Artifact Subspace Reconstruction) was applied [14,15]. Subsequently, all channels were converted to an average reference montage using EEGLAB.…”
Section: Eegmentioning
confidence: 99%
“…This issue could be a rising challenge basically because of the need for cautious removal and cleaning of the signal before any analysis implementation or feature extraction [56]. This issue has attracted the interest of the researchers and various solutions have been proposed over the years [57,58]. The analysis methods for band's feature extraction are the following:…”
Section: Feature Extractionmentioning
confidence: 99%